2015
DOI: 10.1186/s12891-015-0626-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of bilateral Discoid Lateral Menisci (DLM) in patients operated for symptomatic DLM with a follow-up study on their asymptomatic contralateral knees: a Magnetic Resonance Imaging (MRI) assessment

Abstract: BackgroundThe purpose was to investigate prevalence of bilateral discoid lateral menisci (DLM) in Han Chinese patients who received surgery for symptomatic DLM, as well as a follow-up study of their asymptomatic contralateral knees using magnetic resonance imaging (MRI).MethodsA total of 110 patients [50 males and 60 females; average age: 21.95 ± 12.77 years (range: 6 to 67 years)] admitted to our hospital with symptomatic DLM were treated with arthroscopic surgery. The contralateral asymptomatic knees were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Liu et al conducted a follow-up of the asymptomatic knees and found that, 12 out of 66 patients reported occurrence of symptoms in a veyear follow-up, among which 5 showed posterocentral meniscal shift. Therefore, they suggested that prophylactic meniscoplasty may be a better choice for patients with bilateral DLM and undergone detailed physical and radiographical evaluations (23). This study happened to have the same view with Liu and his colleagues (23), and clinical results of follow-ups and plan for conservative treatment were presented in children with unilaterally symptomatic bilateral discoid lateral meniscus operated on the symptomatic side.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Liu et al conducted a follow-up of the asymptomatic knees and found that, 12 out of 66 patients reported occurrence of symptoms in a veyear follow-up, among which 5 showed posterocentral meniscal shift. Therefore, they suggested that prophylactic meniscoplasty may be a better choice for patients with bilateral DLM and undergone detailed physical and radiographical evaluations (23). This study happened to have the same view with Liu and his colleagues (23), and clinical results of follow-ups and plan for conservative treatment were presented in children with unilaterally symptomatic bilateral discoid lateral meniscus operated on the symptomatic side.…”
Section: Resultsmentioning
confidence: 64%
“…Additionally, whether the asymptomatic side of patients with bilateral DLM should receive routine screening and undergo arthroscopy is still being debated. Some studies assessed the asymptomatic knee of the nonoperated side and suggested regular evaluation by MRI and X-rays in follow-ups (18,23,33), and some research mentioned no treatment for children with asymptomatic DLM (24,26,34,35). However, few discussed the reason.…”
Section: Discussionmentioning
confidence: 99%
“…In another study [ 16 ], 79 % of the patients with unilateral SDLM had contralateral DLM. Liu et al [ 17 ] reported that 85 % of bilateral DLM manifested homotype. However, bilateral DLM was often observed with only unilateral occurrence of symptoms [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 Recently, additional studies have reported the prevalence of bilateral DLM to be from 73% to 85% according to bilateral arthroscopic examination or MRI evaluation. [6][7][8] Furthermore, these reports have demonstrated associated meniscus tears on the contralateral side at a rate of 4% to 33% in patients with symptomatic, unilateral surgical DLM. [5][6][7][8] Few studies have identified potential factors that may predict the survivorship of the contralateral meniscus in patients with DLM, however.…”
mentioning
confidence: 96%
“…[6][7][8] Furthermore, these reports have demonstrated associated meniscus tears on the contralateral side at a rate of 4% to 33% in patients with symptomatic, unilateral surgical DLM. [5][6][7][8] Few studies have identified potential factors that may predict the survivorship of the contralateral meniscus in patients with DLM, however.…”
mentioning
confidence: 96%